Acute Effects of Static, Dynamic and Mini-Band Warm-Up Protocols on Some Biomotor Characteristics in Basketball Players - Sedat Okut; Muhammed Zahit Kahraman (Physical Education Theory and Methodology, 2025)
Background. The most effective warm-up programs chosen before training or competition are critically important in terms of performance. This is especially evident in basketball, due to the nature of the game, which requires players to make quick changes of direction and explosive movements.Implementing the most effective warm-up program not only reduces the risk of injury but also ensures that players are fully prepared for the game.